Guest Editors’ Introduction to the Special Section on Human-Centered Computing in Healthcare, Part 1: Defining Criteria and Process - Sean A. Munson; Helena M. Mentis; Katie Siek; Pei-Yi (Patricia) Kuo; Uichin Lee; Laurel D. Riek; Aneesha Singh; Jason Wiese (ACM Transactions on Computing for Healthcare, 2026)
Digital technologies now mediate much of health and care work, but their benefits are unevenly distributed, and research documenting this reaches practice slowly. One reason is that HCI and health evaluate work differently, so papers at their intersection are judged by whichever criteria a reviewer brings from their home community. In this introduction to the ACM HEALTH Continuous Special Section on Human-Centered Computing in Healthcare, we state the criteria we used and where they came from: which people a paper accounts for, whether the health context changes what the paper contributes to computing, whether its methods and any theory suit its question, and what its findings change for design, adoption, or governance. We introduce the eighteen papers in this first installment.